Bidirectional Transformation Enables Hierarchical Nanolaminate Dual‐Phase High‐Entropy Alloys. Issue 44 (14th September 2018) - Lu, Wenjun; Liebscher, Christian H.; Dehm, Gerhard; Raabe, Dierk; Li, Zhiming
Abstract: Microstructural length‐scale refinement is among the most efficient approaches to strengthen metallic materials. Conventional methods for refining microstructures generally involve grain size reduction via heavy cold working, compromising the material's ductility. Here, a fundamentally new approach that allows load‐driven formation and permanent refinement of a hierarchical nanolaminate structure in a novel high‐entropy alloy containing multiple principal elements is reported. This is achieved by triggering both, dynamic forward transformation from a faced‐centered‐cubic γ matrix into a hexagonal‐close‐packed ε nanolaminate structure and the dynamic reverse transformation from ε into γ. This new mechanism is referred to as the "bidirectional transformation induced plasticity" (B‐TRIP) effect, which is enabled through a near‐zero yet positive stacking fault energy of γ. Modulation of directionality in the transformation is triggered by local dissipative heating and local micromechanical fields. The simple thermodynamic and kinetic foundations for the B‐TRIP effect render this approach generally suited for designing metastable strong and ductile bulk materials with hierarchical nanolaminate substructures. Abstract : A new mechanism, termed, the "bidirectional transformation induced plasticity" effect (B‐TRIP), allows load‐driven formation and permanent refinement of hierarchical nanolaminates in a dual‐phase high‐entropy alloy. The B‐TRIP effect is enabled through a near‐zero yet positive stacking fault energy of the matrix phase, and hence modulation of directionality in the transformation is triggered by local dissipative heating and local stress–strain fields.